2020
DOI: 10.1111/codi.15237
|View full text |Cite
|
Sign up to set email alerts
|

Exploring shared surgical decision‐making from the patient's perspective: is the personality of the surgeon important?

Abstract: Aim The aim was to determine the importance of a colorectal surgeon's personality to patients and its influence on their decision-making. Methods We present a two-part mixed methods study using the Guidance for Reporting Involvement of Patients and the Public (GRIPP-2) long form. Part 1 was an online survey (25 questions) and Part 2 a faceto-face patient and public involvement exercise. Part 1 included patient demographics, details of surgery, overall patient satisfaction (net promoter score) and patient views… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The common surgical traits described in this review may be considered advantageous in establishing rapport with patients and, perhaps, contradicts the 'surgeon stereotype' of rudeness, aggression and being difficult to work with [39]. Patients have previously indicated that they believe that surgeon personality influences surgical decision-making (including informed consent and communication of treatment options) as well as the surgeon's response to post-operative complications [40]. Whilst we do not advocate personality testing as a recruitment strategy for trainee selection, the authors hypothesise that periodic personality testing of surgeons throughout their career (given that personality changes with age and experience) may facilitate continuing professional development via multiple methods, for example, targeted non-technical skills training for surgeons, and also aid identification of surgeons at risk of work-related stress or burnout with timely occupational health interventions [41].…”
Section: Discussionmentioning
confidence: 99%
“…The common surgical traits described in this review may be considered advantageous in establishing rapport with patients and, perhaps, contradicts the 'surgeon stereotype' of rudeness, aggression and being difficult to work with [39]. Patients have previously indicated that they believe that surgeon personality influences surgical decision-making (including informed consent and communication of treatment options) as well as the surgeon's response to post-operative complications [40]. Whilst we do not advocate personality testing as a recruitment strategy for trainee selection, the authors hypothesise that periodic personality testing of surgeons throughout their career (given that personality changes with age and experience) may facilitate continuing professional development via multiple methods, for example, targeted non-technical skills training for surgeons, and also aid identification of surgeons at risk of work-related stress or burnout with timely occupational health interventions [41].…”
Section: Discussionmentioning
confidence: 99%
“…It is with great interest that I read the article by Bisset et al in this month's issue of Colorectal Disease [1]. This study builds on previous work by Moug et al, which showed that colorectal surgeons are more likely to demonstrate high levels of emotional stability and conscientiousness in comparison with a non-clinical population [2].…”
mentioning
confidence: 76%
“…Interestingly, this finding persists despite controlling for surgeon effect between different providers. Bisset et al [25] describe how surgeon personality and communication style directly influence the SDM process. Thus, the effect of social deprivation on the patient–physician relationship is one that warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%